A Ketepatan Penentuan Kode Diagnosis Utama Penyebab Kematian Pada Kasus Stroke Di RSUD Brigjend H. Hasan Basry Kandangan - Nina Rahmadiliyani Rahmadiliyani; Aida Fitria (HB PRESS, 2019)
World Health Information (WHO) establishes a set of rules or procedures that must be followed for granting kodefikasi UCoD determination of the code on certificate of death must pay attention to the sequence of events leading to the death of the disease and the cause of the beginning of the sequence such. Some hospitals are not doing the coding causes of death and inaccuracies in coding causes of death data produces the wrong health. This research aims to know the description of accuracy determination of main diagnosis codes cause of death in the case of a stroke in a hospital Brigjend H.Hasan Basry Kandangan. This research use descriptive qualitative research methods with quantitative studies. This research was conducted with observation 68 medical record documents and interviewing doctors, koder and head installation medical record as supporting in this research. In this research note the hospital does not have an SOP and the absence of writing the cause of death on a death certificate so as not to kodefikasi the implementation and reporting of the implementation of the hospital not be RL4 about mortality reporting.